Estandarización de tiempos y métodos de trabajo para el incremento de la productividad en los procesos de operación del taller de enderezada y pintura "PINTU CAR". - Casa Monta, Darío Xavier (2020)
The purpose of this research is to standardize working times and methods for increasing productivity in the operational processes at the "PINTU CAR" straightening and painting workshop. The researchers analyzed the productive efficiency of the current workforce through the method of direct observation and time-taking, to subsequently propose a proposal for time standardization. This study is a research project, in which a field modality is adopted applying techniques such as observation, interviews, and timing to evaluate the production process of the workshop. The results obtained allowed the researchers to identify the operational problems for each stage of the process as well as the low productivity due to the low efficiency and downtime in the workforce in which a standard time limit was not established in the vehicle repair operations. For the information gathering, the work-study method was used, where the factors in the production process were analyzed giving priority to the current time-taking of the activities carried out by zero-time timing; then times were established of each process obtaining a current total time for reparation with severe damage of 2516.1 minutes, with average damage of 878.2 minutes and with slight damage of 478.6 minutes. For the reduction of time, a proposal for standardization of time in the areas of straightening, surface preparation, and vehicle painting is proposed, which is intended to increase the efficiency of workers. Activities were also combined using the man-machine diagram, which allowed reducing downtimes that did not add any value to the processes, as well as other proposals for improvement such as a redesign of the workshop's layout through an activity path diagram to reduce times and distances by increasing the monthly productivity of the workshop. It is concluded that in the workshop it was possible to increase the productivity of the workforce in severe damage by 8.61%, in average damage by 15.79%, and in slight damage by17.40% due to the times are standardized, so there is an established time range for each activity of the straightening and painting processes of the "PINTU CAR" workshop.